Assessment of toxicity of cadmium and lead in tomato - Bertoli, Alexandre Carvalho; Carvalho, Ruy; Cannata, Marcele Gabriel; Bastos, Ana Rosa Ribeiro; Augusto, Amanda dos Santos (Eclética Química, 2014)
Having the objective of evaluating the effect of application of cadmium and lead in tomato in the content, rate of growth and translocation in different parts of the plant, tomato plants were grown in nutrient solution of Clark and submitted to rising doses of Pb: 0; 0,25; 1,0; 5,0 and 10,0 mg L-1. Cadmium translocated 21,9% to more than lead to the aerial part showing Pb concentrated in the roots while in the fruits, the translocation of these metals reached 1,89% for Cd and 1,38% for Pb. In relation to the control treatment, the fruits production was reduced from the concentration 5,0 mg L-1 de Pb and 1,0 mg L-1 of Cd.